NAT10 promotes ovarian cancer cell migration, invasion, and stemness via N4-acetylcytidine modification of CAPRIN1 - Yang Song; Min Cheng (BMC Women's Health)
Abstract Ovarian cancer (OC) is the most lethal gynecological tumor. N4-acetylcytidine (ac4C) modification, catalyzed by the acetyltransferase NAT10, is involved in the occurrence and development of cancers. This study aimed to investigate the role of NAT10 in OC and the underlying molecular mechanisms. The expression of NAT10 and CAPRIN1 in OC cells lines were measured using quantitative real-time polymerase chain reaction and immunoblotting. Biological behaviors of OC cells were evaluated using EdU, Transwell, sphere formation, and immunoblotting assays. The molecular mechanism of NAT10 function was analyzed using bioinformatics, ac4C- RNA immunoprecipitation, and actinomycin D treatment assay. The effect of NAT10 on OC progression in vivo was evaluated using xenograft tumor model. The results indicated that NAT10 and CAPRIN1 were highly expressed in OC cells. NAT10 knockdown suppressed OC cell proliferation, migration, invasiveness, stemness, and epithelial-mesenchymal transition in vitro, and impeded tumor growth in vivo. Additionally, CAPRIN1 expression was found to be positively related to NAT10 expression in OC. Silencing of NAT10 inhibited ac4C levels of CAPRIN1 and reduced its RNA stability. Moreover, overexpression of CAPRIN1 reversed the suppression of migration, invasion, and stemness caused by NAT10 knockdown, while knockdown of CAPRIN1 alone inhibited these malignant behaviors of OC cells. In conclusion, NAT10 promotes OC progression by promoting cellular migration, invasion, and stemness via upregulating CAPRIN1 expression. Mechanistically, NAT10 stabilizes CAPRIN1 by promoting its ac4C modification. These findings suggest that NAT10 may be a promising therapy target for OC. Graphical abstract